Uova fatali. II: Il sistema scenico-drammatico neosovietico russo negli anni della formazione (1924-1928) - Lenzi, Massimo (Mimesis Journal, 2021)
This is the second part of an essay aimed at reconstructing the typologies, institutions and structures of the Russian-language theatre-drama production system in the early years of the Soviet State (1924-1928), as well as the activities of the main protagonists who worked in that system at that time. In particular, following the theme of the relations between the Art Theatre and its main Studies, with which the first part closed, this second part considers its stylistic repositioning with respect to the hegemony exercised by the institutions led by Meyerhold, also analysing the productions within which that hegemony reached its apogee in those years.